2007
DOI: 10.1177/159101990701300204
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor Cerebri: A New Door Opens for Treatment

Abstract: Pseudotumor cerebri remains a scarcely known pathology. We present the experience of a multidisciplinary working group which studied this disorder focusing on the venous alterations of the dural sinuses. Seventeen cases were studied, diagnosed, controlled and treated by our team. In one of the cases, we placed a stent in the left lateral sinus with good result. In all the patients we observed various degrees of stenosis in the brain venous sinuses quantified by pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…1). 2,6,7,[10][11][12][13][14][15][16]18,19,[21][22][23]25,28,29,[31][32][33][34][35][36][37][38][39][42][43][44] As a group, the venous pressure gradients across the stenotic segments ranged from 2 to 77 mm Hg with a mean of 22.1 mm Hg. The mean duration of clinical follow-up was 18.3 months.…”
Section: Resultsmentioning
confidence: 99%
“…1). 2,6,7,[10][11][12][13][14][15][16]18,19,[21][22][23]25,28,29,[31][32][33][34][35][36][37][38][39][42][43][44] As a group, the venous pressure gradients across the stenotic segments ranged from 2 to 77 mm Hg with a mean of 22.1 mm Hg. The mean duration of clinical follow-up was 18.3 months.…”
Section: Resultsmentioning
confidence: 99%
“…When 2 studies appeared to consist of mostly overlapping patient sets, only the larger study was used whenever possible. In total, 49 studies with 4 or more stented patients (4 prospective 19,[25][26][27] and 45 retrospective 20,21, ) and 18 reports with 1-3 patients [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] were found, yielding a total of 1,626 IIH patients treated with venous stenting. Figure 1 details a demonstrative case in which a worsening of visual fields despite medical treatment led to the decision to advance to venous stenting.…”
Section: Meta-analysis Of Outcomes Data For Venous Stenting For Idiop...mentioning
confidence: 99%
“…However, two (16.6%) cases were entirely "headache-free;" surprisingly, this finding was not discussed further. [11] De Simone et al[12] reported on two PTCS patients without headache. They concluded that the lack of headache in one patient may reflect an inherited condition of protection against neurovascular headache development, since neither the patient nor her first-degree relatives reported headache in their lives.…”
Section: Suggested Pseudotumor Cerebri Syndromementioning
confidence: 99%